Can Women’s Empowerment Increase Their Participation in the Workforce? Evidence from ASEAN - Maida Shafarana Shabrina; Sitti Retno Faridatussalam (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to examine the impact of women's empowerment on female labor force participation in ASEAN countries. Women's empowerment is measured through variables such as education, health, wages, parliamentary representation, fertility rates, and maternal mortality rates.Method: This research employs a panel data approach by applying the Random Effects Model (REM) across 10 ASEAN member countries. Socio-economic and demographic indicators are integrated to assess the extent to which these variables influence female labor force participation.Result: Research findings indicate that education, access to healthcare services, and low maternal mortality rates positively contribute to increasing women's labor force participation. Conversely, factors such as low wage levels, limited female representation in parliament, and high fertility rates serve as barriers.Practical Implications for Economic Growth and Development: This study identifies key factors influencing female labor force participation and provides strategic recommendations for policymakers in the ASEAN region. Improving women's access to education and healthcare services is expected to foster inclusive development, reduce gender disparities, and strengthen the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of gender equality and decent work.Originality/Value: This study makes a novel contribution by incorporating rarely discussed variables such as maternal mortality rates and fertility levels in a region characterized by diverse socio-economic conditions. It offers deeper insights into the driving forces behind female labor force participation in ASEAN countries.